Removal of Separated Endodontic K-File with the Aid of Hypodermic Needle and Cyanoacrylate - Luciana Maria Arcanjo Frota; Bernardo Almeida Aguiar; Maria Gerusa Brito Aragão; Bruno Carvalho de Vasconcelos (Case Reports in Dentistry)
A wide range of accidents might happen during the treatment of the root canal system, where the instrument separation is one of the most unpleasant occurrences. Several techniques have been developed to facilitate the removal of the fragments; however, they generally require specific devices that not always are available to the clinician. The aim of this case report is to present a simple alternative technique to remove from the root canals manual instruments fractured during the treatment. The case has its outline based on a 31-year-old patient who sought the clinic to have her maxillary first left premolar rehabilitated. The clinic and radiographic examinations revealed the need of endodontic retreatment and the presence of a fragment of a K-file instrument localized at the apical third of the palatine canal. The retreatment was initiated by the removal of the obturation materials followed by several unsuccessful attempts to take out the fractured instrument. Hence, it was chosen to perform the fragment removal using a hypodermic needle and cyanoacrylate adhesive. The fragment easily came out, which reinforces the technique adopted as a safe, simple, and low cost mean to solve the problem of fractured instruments using only items already present in the endodontic arsenal.